2019
DOI: 10.1111/jpy.12819
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 5‐azacytidine and cadmium on global 5‐methylcytosine content and secondary metabolites in the freshwater microalgae Chlamydomonas reinhardtii and Scenedesmus quadricauda

Abstract: Epigenetic changes are important mechanisms in the regulation of chromatin structure and gene expression. Cytosine methylation is one of the major epigenetic modifications, mediated by DNA methyltransferases, which transfer methyl groups from S‐adenosyl‐L‐methionine (SAM) to the fifth carbon of cytosine. Various external environmental conditions can change the global hypo/hypermethylation pattern of DNA. These alterations may affect the organism's response to stress conditions. In this study, for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…The SmDMLs (DEMETER-like DNA glycosylases) expression was downregulated by 5-azaC treatment in Salvia miltiorrhiza, in which the tanshinone content was increased significantly (Jiang et al, 2018;Li et al, 2018), suggesting that the tanshinone accumulation was pronounced by 5-azaC induced DNA demethylation. The effect of 5-azaC on secondary metabolites accumulation and genes expression was also confirmed in Chlamydomonas reinhardtii (Bacova et al, 2019), Dendrobium (Ni et al, 2014), and Pogostemon cablin (Luo et al, 2021). In summary, we speculated that the upregulation of DXS, DXR, GPPS, G10H, and 10HGO induced by 5-azaC treatment was involved in the iridoid glycoside accumulation in R. glutinosa.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The SmDMLs (DEMETER-like DNA glycosylases) expression was downregulated by 5-azaC treatment in Salvia miltiorrhiza, in which the tanshinone content was increased significantly (Jiang et al, 2018;Li et al, 2018), suggesting that the tanshinone accumulation was pronounced by 5-azaC induced DNA demethylation. The effect of 5-azaC on secondary metabolites accumulation and genes expression was also confirmed in Chlamydomonas reinhardtii (Bacova et al, 2019), Dendrobium (Ni et al, 2014), and Pogostemon cablin (Luo et al, 2021). In summary, we speculated that the upregulation of DXS, DXR, GPPS, G10H, and 10HGO induced by 5-azaC treatment was involved in the iridoid glycoside accumulation in R. glutinosa.…”
Section: Discussionmentioning
confidence: 82%
“…DNA methylation could affect plant growth and development (Candaele et al, 2014 ; Yamamuro et al, 2014 ; Zhou W. et al, 2016 ), SMs accumulation, and the expression of synthetase gene associated with SMs (Qi et al, 2016 ; Wang B. et al, 2018 ; Wang et al, 2019 ). Studies have shown that the gene expression of the secondary metabolic biosynthesis pathway was upregulated under 5-azaC (a DNA methylation inhibitor) treatment (Ni et al, 2014 ; Jiang et al, 2018 ; Li et al, 2018 ; Bacova et al, 2019 ; Luo et al, 2021 ). In our research, under 15 and 50 μM 5-azaC treatment, the expression of DXS, DXR, GPPS, G10H , and 10HGO was upregulated in root and leaf, especially 50 μM ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy metals (HMs) are significant environmental pollutants, and their toxicity is a problem of increasing significance for ecological, evolutionary, nutritional and environmental reasons [ 97 , 98 ]. Despite low concentrations of iron (Fe), vanadium (V), zinc (Zn) and molybdenum (Mo) are essential to carry out cellular functions of algae [ 99 , 100 ]; the same metals at high concentrations, also including the unessential HMs, such as arsenic (As), cadmium (Cd), chromium (Cr), lead (Pb) and mercury (Hg), cause blockages of the cell division, reduction in photosynthesis and inhibition of various thiol-group-containing enzyme activities [ 101 , 102 , 103 ].…”
Section: Dna Methylation In Algae Response To Abiotic Stressmentioning
confidence: 99%
“…However, the minimal data in the literature about algal DNA methylation in response to HMs stress, concern only Cd and Cr [ 82 , 102 , 103 , 107 ].…”
Section: Dna Methylation In Algae Response To Abiotic Stressmentioning
confidence: 99%